Swapping identity

Algebra Level 4

In an arithmetic progression, the sum of the first 1001 terms is equal to 29, and the sum of the first 29 terms is equal to 1001.

Find the sum of the first 1030 terms of this arithmetic progression.


The answer is -1030.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let's generalize this. Let m = 1001 m = 1001 , n = 29 n=29 , and a a , d d and S k S_k be the first term, common difference and sum of first k k terms of the AP. Then, we have:

{ S m = m [ 2 a + ( m 1 ) d ] 2 = n 2 m n a + m n ( m 1 ) d = 2 n 2 . . . ( 1 ) S n = n [ 2 a + ( n 1 ) d ] 2 = m 2 m n a + m n ( n 1 ) d = 2 m 2 . . . ( 2 ) \begin{cases} S_m = \dfrac{m[2a+(m-1)d]}{2} = n & \Rightarrow 2mna + mn(m-1)d = 2n^2 & ...(1) \\ S_n = \dfrac{n[2a+(n-1)d]}{2} = m & \Rightarrow 2mna + mn(n-1)d = 2m^2 & ...(2) \end{cases}

( 1 ) ( 2 ) : m n ( m n ) d = 2 ( n 2 m 2 ) d = 2 ( m + n ) m n \begin{aligned} (1)-(2): \quad mn(m - n)d & = 2(n^2-m^2) \\ \Rightarrow \color{#3D99F6}{d} & = \color{#3D99F6}{-\frac{2(m+n)}{mn}} \end{aligned}

Now we need to find:

S m + n = ( m + n ) [ 2 a + ( m + n 1 ) d ] 2 = m [ 2 a + ( m 1 ) d + n d ] 2 + n [ 2 a + ( n 1 ) d + m d ] 2 = S m + m n d 2 + S n + n m d 2 = n + m + m n d = n + m m n ( 2 ( m + n ) m n ) = ( m + n ) S 1030 = S 1001 + 29 = 1030 \begin{aligned} S_{m+n} & = \dfrac{(m+n)[2a+(m+n-1)d]}{2} \\ & = \dfrac{m[2a+(m-1)d + nd]}{2} + \dfrac{n[2a+(n-1)d+md]}{2} \\ & = S_m + \dfrac{mnd}{2} + S_n + \dfrac{nmd}{2} \\ & = n + m + mn\color{#3D99F6}{d} \\ & = n + m - mn\left(\color{#3D99F6}{\frac{2(m+n)}{mn}}\right) \\ & = -(m+n) \\ \Rightarrow S_{1030} & = S_{1001+29} = \boxed{- 1030} \end{aligned}

Excellent way!!

Dev Sharma - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...